Unveiling The Relation Between Product Placement and Consumer Minds in the ‘Stranger Things’ Series - Boer, Reina Amerya Ayu (Journal of Research on Business and Tourism, 2024)
Product placement is a marketing strategy that involves the integration of branded products into media content. One of the most popular TV series that effectively uses product placement is ‘Stranger Things’, created by The Duffer Brothers. This paper analyzes the impact of product placement on consumer behavior in the context of the ‘Stranger Things’ series. This paper examines the brands that have been featured in the series, the value of their placement, and the effect on consumer behavior. This research uses traditional literature reviews, with analyzing data and journals as the main sources of data. The findings revealed that the appearance of branded products in the series has increased brand awareness and recall among viewers. The paper concludes that product placement in ‘Stranger Things’ has been a successful marketing strategy that has influenced consumer behavior and it is a step that future marketers should consider.